(untitled) (Journal of Hama University, 2020)
The study examined the role of relaxation in reducing the symptoms and traumatic experiences in a sample of displaced adolescents in Damascus Governorate. The aim of the research was to uncover the effectiveness of relaxation in reducing the symptoms of traumatic experiences. The research consisted of two theoretical and practical frameworks. The research was applied on a sample of the second grade secondary school students, consisted of (12) male and female students. Through the theoretical framework, it provided the theoretical background for the topic of relaxation. As for the practical framework, it presented the stages of carrying out the semi-experimental work and a review of the findings of the research, including presentation, analysis, and interpretation, through which these results were obtained, and we reached some suggestions, The data was statistically processed using some of the necessary statistical laws such as the Welcocson test to know the effect of relaxation and determine its effectiveness. The aim of the research was to prepare and apply a proposed program for relaxation on the individuals of the research sample and to identify the impact of the proposed program in reducing the severity of symptoms of traumatic experiences among displaced teenagers in the city of Damascus. The most important results were the positive effect of relaxation, due to the effectiveness of relaxation, after research showed that the prevalence of symptoms of traumatic experiences experienced by displaced teenagers reached 13.2%. As for the symptoms of experiences of abandoned adolescents, the symptoms of restoration have acquired the highest value, followed by symptoms of arousal and then symptoms.